2009
DOI: 10.4047/jap.2009.1.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proximal contact strength by postural changes

Abstract: STATEMENT OF PROBLEMProper proximal contact is important for maintaining and stabilizing the dental arch. However, the proximal contact strength (PCS) is not a constant value and can be affected by a variety of factors.PURPOSEThis study examined the influences of postural changes on the posterior PCS.MATERIAL AND METHODSTwelve adults with a normal occlusion and had not undergone prosthetic treatment or proximal restoration were participated in this study. A metal strip was inserted into the proximal surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
(29 reference statements)
1
8
0
2
Order By: Relevance
“…Findings from this study cannot be directly compared with those reported previously as similar studies are lacking. Research involving shim stock has focused primarily on measuring the interproximal contact force, [15][16][17][18] and the use of different shim stock thicknesses, different measuring devices, and different clinical questions has led to results that cannot be compared with those reported in this study. Similarly, floss [19][20][21] and articulating film 22,23 have been used to evaluate different restorative procedures and materials, but direct comparisons with the results of the present study are not possible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Findings from this study cannot be directly compared with those reported previously as similar studies are lacking. Research involving shim stock has focused primarily on measuring the interproximal contact force, [15][16][17][18] and the use of different shim stock thicknesses, different measuring devices, and different clinical questions has led to results that cannot be compared with those reported in this study. Similarly, floss [19][20][21] and articulating film 22,23 have been used to evaluate different restorative procedures and materials, but direct comparisons with the results of the present study are not possible.…”
Section: Discussionmentioning
confidence: 95%
“…12 Previous assessments of interproximal contact have focused primarily on unrestored teeth or teeth containing direct restorative materials. [2][3][4][5]8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] The authors are unaware of evidence-based reports that have evaluated the best methods for assessing the tightness of interproximal contacts of crowns. This study was conducted to provide information by comparing 3 different evaluation methods in which the interproximal distance was controlled by varying the crown width.…”
mentioning
confidence: 99%
“…Foi possível perceber que sistemas que utilizam anéis de separação 6,8,9,12 vem ganhando espaço e se mostrando uma alternativa viável e promissora. Porém, postura e limitações de adaptação do operador durante o preparo da área de contato foram citadas como complicações 16 .…”
Section: Complicação Associada Relatada Conclusãounclassified
“…Moreover, the mandible position is determined by dental occlusion, the relative position of teeth to each other 8 , 9 ) . In addition, some studies have found that the stomatognathic system and mandible disorders can influence the spine 10 , 11 ) . Tecco et al also observed that the loading percentage and the loading surface on the right and the left feet were influenced by an experimentally induced imbalance of occlusion created by a cotton roll positioned in dental arches 12 ) .…”
Section: Introductionmentioning
confidence: 99%